Vaginal microbiome dysbiosis and sexually transmitted infections correlate with concentrations of immunoglobulin isotypes in human cervicovaginal mucus: insights into HIV-1 transmission - Akiso, Matrona M.; Abook, Israel; Mureithi, Marianne W.; Kombo, Janet; Koi, Print; Musando, Joel; Chirchir, Ruth J.; McRaven, Michael D.; Carias, Ann M.; Joseph, Sarah; Anzala, Omu; Hope, Thomas J. (Frontiers in Immunology, 2025)
IntroductionLittle is known about the relationship between antibody isotype in cervicovaginal mucus (CVM) and the local microenvironment and how this impacts HIV-1 transmission at the female genital mucosa.MethodsIn a cohort of 139 adult women in Kenya, we measured antibody isotypes in CVM and describe their associations with local pH, serum concentrations of estrogen and progesterone, and sexually transmitted infections (STIs), including HIV-1.ResultsWe found that immunoglobulin G2 (IgG2) was the most abundant and IgG4 was the least abundant in the CVM. Overall, IgG1 concentrations were significantly lower in CVM samples from women with bacterial vaginosis (BV) compared to those without BV. Among women with BV, IgG1 concentrations declined further as vaginal pH increased, suggesting possible pH-mediated degradation. We also report negative associations of BV status with IgG3 and IgG4. In addition, infection with Mycoplasma genitalium and Neisseria gonorrhoeae was positively associated with concentrations of IgA and IgM, respectively. We also found the relationship between antibody isotype and subclasses with HIV-1 viral mobility in vitro. IgG3 concentrations negatively correlated with CAP045 HIV-1 mobility and IgG1 concentrations negatively correlated with the mobility of the 92TH023 recombinant HIV-1 strain upon VRC01 depletion. These observations point towards a potentially protective role for IgG1 and IgG3 in trapping certain HIV-1 strains in the CVM.DiscussionImportantly, our study builds on previous work, providing a potential mechanism by which BV and STIs may modulate immunoglobulin isotype and subclass content in the CVM. These results highlight the need for proper treatment of BV and other STIs, as this could impact the effectiveness of HIV-1 vaccines targeted at enhancing specific immunoglobulin responses in the cervicovaginal mucosa.